Moralitas Publik Sebagai Dasar Pembenar Terhadap Kewajiban Sertifikasi Halal Produk Makanan Di Indonesia Berdasarkan GATT-WTO 1994 - Ruhaeni, Neni; Aqimuddin, Eka An; Afriyadi, Hadian (UI Scholars Hub, 2022)
In principle, World Trade Organization (WTO) prohibit each member states to make policy, both tarrif and non tarrif, which potentially disturb international trade. Nevertheless, there are exceptions that can be used by the state as a basis for justification to hold trade policy which consider contratry to WTO law. One of them is to protect public morality. The Halal Product Assurance Act (UUJPH) stipulate obligation of halal certification for food products that enter, circulate and trade in Indonesia. This act is considered as a protective and discriminatory policy. This research founds that although some provisions in UUJPH are discriminatory and contrary to WTO Law, it can be argued that those provisions were made in order to protect public morality in Indonesia and its justified under the law itself.